Acoustic power of fluid-loaded circular plate located in finite baffle - LENIOWSKA, L. (Archives of Acoustics, 1997)
The oblate spheroidal coordinate system was used for calculation of the acoustic power radiated by a thin circular plate located in a finite baffle. It was assumed that the plate was clamped at the circumference of the planar limited baffle and radiated into lossless homogeneous liquid medium. The vibrations of the plate were forced by time harmonic external pressure. The damping effects caused by internal friction in the plate material as well as dynamic influence of the waves emitted by the plate were taken into consideration. The formula for the acoustic power was derived by the application of properties of eigenfunctions of plate equation of motion.